2023
DOI: 10.1039/d3sm00812f
|View full text |Cite
|
Sign up to set email alerts
|

Roles of aqueous nonsolvents influencing the dynamic stability of poly-(n-butyl methacrylate) thin films at biologically relevant temperatures

Jotypriya Sarkar,
Mithun Madhusudanan,
Chandni V. C.
et al.

Abstract: Poly-(n-butyl methacrylate) (PnBMA) is an important polymer in biomedical applications. Here we study the stability of PnBMA thin films prepared on top of slippery silicon substrates and exposed to nonsolvent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
(136 reference statements)
0
0
0
Order By: Relevance
“…Thus, the addition of plasticizer resulted in a reduction in modulus and viscosity but enhanced σ rec . Later, Sarkar et al showed that incubation of the polymer film in nonsolvents can also affect the stability of the film.…”
Section: Characterization Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the addition of plasticizer resulted in a reduction in modulus and viscosity but enhanced σ rec . Later, Sarkar et al showed that incubation of the polymer film in nonsolvents can also affect the stability of the film.…”
Section: Characterization Methodologiesmentioning
confidence: 99%
“…Thus, the addition of plasticizer resulted in a reduction in modulus and viscosity but enhanced σ rec . Later, Sarkar et al 268 showed that incubation of the polymer film in nonsolvents can also affect the stability of the film. Dewetting as a characterization technique has been explored very well in literature to establish it as a nanorheology tool.…”
Section: Defined a Preparation Parameter ( = T Eq Prepmentioning
confidence: 99%
See 1 more Smart Citation